(untitled) (Research, Society and Development, 2018)
With the expansion of educational policies, the literacy process was complemented by the literacy concept and, in particular, in the contexts surrounding Special Education. Since it is relevant and part of teaching and the student learning process, the present study aimed to investigate what has been researched in the main special education periodicals on this theme of literacy and literacy for students with intellectual disabilities in the last ten years. The research brings a bibliographic review using as data source two periodicals of great potential in the area of Special Education being: Brazilian Journal of Special Education - Brazilian Association of Special Education Researchers (ABPEE) and Special Education Journal (UFSM) -line. A total of 12 articles were selected, 3 in the Special Education Journal and 9 in the Brazilian Journal of Special Education. The results pointed out important gaps to be researched in the area and it is hoped to contribute to the area of literacy and literacy of students with intellectual disabilities. We conclude that, because it is a relevant and current topic in the Brazilian context, future studies of a systematic review of this literature to complement the results found here would be suggestive.